Students Problematics in Facing P5 Projects in Social Studies Subjects at Junior Highschool (SMP) Negeri 16 Kota Bengkulu - Dia Pransiska; Desy Eka Citra Dewi; Sepri Yunarman (UIN Fatmawati Sukarno Bengkulu, 2026)
The Pancasila Student Profile Strengthening Project (P-5) is one of the national programs applied to educational units, including in junior high school social studies subjects. Social studies education has a high relevance to P5 in terms of objectives and subject matter. But in its implementation P5 still faces many obstacles. This study aims to analyze the problems faced by students in the implementation of P5 in SMP Negeri 16 Bengkulu City. The research was conducted using descriptive qualitative method. The objects of research are students, teachers and the person in charge of the project. Data were collected through interviews, questionnaires and documentation and then analyzed using the Milles and Huberman model. The results showed that there were 4 main problems for students in implementing P5 in SMP negeri 16 Bengkulu City, namely: limited facilities and resources; 2) lack of support from parents and external parties; 3) many other tasks outside the project; and 4) technical obstacles. From these results it can be concluded that the implementation of P5 in social studies learning at SMP Negeri 16 Bengkulu City has been running but still faces obstacles that need to be resolved by the teachers and the school.